Sedimentation Patterns of Fine-Grained Particles in the Dam Area of the Three Gorges Project: 3D Numerical Simulation - Jia, Dong-dong; Shao, Xue-jun; Zhang, Xing-nong; Ye, Yun-tao (Journal of hydraulic engineering (New York, N.Y.), 2013)
AbstractThis paper is focused on the sedimentation processes of fine-grained particles in a 14-km-long section upstream of the Three Gorges Dam, referred to as the dam area, during the period from March 2003 to October 2006. Field measurements indicated that sediment deposits in the dam area were mostly found at the bottom of the main channel, where a new river bed was formed with a flat, nearly horizontal surface. In contrast, very little deposits could be found on the bank slopes of the channel. The observations disagree with the previous predictions based on numerical models, which suggested more evenly distribution of deposits over the cross section. This paper explains the discrepancy by identifying the motion of muddy deposits by gravity as a key process in the dam area. A three-dimensional (3D) full Reynolds-Averaged Navier-Stokes (RANS) model is applied to calculate the flow and sediment transport processes. A critical slope method (CSM) is used to estimate the downslope movement of muddy deposits in the bottom by gravity. The formation of bottom deposits is successfully simulated using this approach. The simulated sedimentation patterns agree well with field observations.